EFFECT OF GROSS REGIONAL DOMESTIC PRODUCT MINIMUM WAGES AND INVESMENT TO MANPOWER IN WEST BORNEO - B2051142010, SABINA SALAWATI (Jurnal Ekonomi Daerah (JEDA), 2016)
The successful achievement of the welfare of a nation can be measured by the extent to which a country can solve a variety of problems that are being faced. one of them basic problems confronting in employment of this started by the high employment a result of growth of population many cause offer manpower will increase. The high offer labor not in sent with absorption of workers have also high. Besides manpower is an important factor in supporting economic development undertaken by developing countries in order to create aquitable economic development. So researchers are interested in writing a research on the factor of absorption of manpower where gross regional domestic product, minimum wages and investment. This study aims to analyze effect of gross regional domestic product, minimum wages and investment to manpower in west borneo in the year 2010 to 2014. This study uses a quantitative and qualitative analysis with explanatory descriptive method.Â This Data used the panel (cross section and time series) through a linear regression multiple regression (multiple) to technique teknik Estimation General Least Square (EGLS), Fixed Effect Model (FEM) using the tools eviews program. Observation data about 60 in 12 district / city in west borneo during the period 2010 until 214. The result of this research showed that gross domestic product influential negative and not significantly to the absorption of manpower in west borneo, while minimum wage influential positive and significant against to the absorption of manpower in west borneo and investment influential negative and not significantly to the absorption of manpower in west borneo. Keywords : Gross Regional Domestic Product, Minimum Wage, Investment, Manpower Absorption